An Analysis of English Speaking Difficulties in First-Semester Students - Izzati Suhaila; Rizki Nurhidayah Sitompul (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates the various speaking difficulties faced by English as a Foreign Language (EFL) students, with a particular focus on Management and Accounting students. Despite having several years of formal English education, many students still struggle to communicate effectively and confidently in spoken English. This situation highlights a significant gap between classroom instruction and students’ actual communicative competence. The study aims to identify the root causes of these challenges and examine how linguistic and psychological factors interact to hinder students’ oral performance. These psychological factors are often reinforced by the lack of adequate speaking practice both inside and outside the classroom, resulting in limited exposure to authentic language use. The findings indicate that students’ speaking difficulties are not solely rooted in linguistic deficiencies, but are strongly influenced by affective factors and insufficient communicative interaction. Therefore, the study recommends that speaking instruction integrate more interactive and student-centered activities, such as group discussions, role-plays, and task-based speaking tasks, in order to create a more supportive and engaging learning environment. Additionally, teachers are encouraged to provide positive feedback and foster an atmosphere that allows students to feel comfortable taking risks when using English.